The Significance of Natural Environment in Reducing Long-Term Consequences of COVID-19. Tasks and Threats of Forest Pedagogy as Environmental Education - Baranowska, Marlena; Koprowicz, Anna; Korzeniewicz, Martyna; Korzeniewicz, Robert (Studia Ecologiae et Bioethicae, 2023)
During COVID 19 pandemic- related restrictions it was observed that people were more willing to spend time in nature and the thus number of forest visitors doubled. It has been proven that communing with nature reduces symptoms of anxiety, depression, alleviates stress, improves concentration and vitality. It also strengthens the immunological response of the body and reduces the risk of cardiovascular diseases and obesity. Being in nature encourages people to show prosocial behaviour, strengthens social bonds, and even reduces the level of violence. There is a connection between lowering blood serum levels of cortisol, dopamine and norepinephrine and spending a significant amount of time in nature. Walking in the forest can be effective in mitigating the effects of the COVID-19 pandemic. The aim of the study was to summarize the long-term consequences of the COVID-19 pandemic, while indicating the therapeutic properties of the forest that can prevent or mitigate the effects of the disease caused by the SARS-CoV-2 virus. In addition, it was indicated what are the possibilities and tasks of forest pedagogy in encouraging people to take advantage of the benefits of forest recreation.